Harnessing the early post-injury inflammatory responses for cardiac regeneration. Issue 1 (December 2017) - Cheng, Bill; Chen, H.; Chou, I.; Tang, Tony; Hsieh, Patrick
Abstract Cardiac inflammation is considered by many as the main driving force in prolonging the pathological condition in the heart after myocardial infarction. Immediately after cardiac ischemic injury, neutrophils are the first innate immune cells recruited to the ischemic myocardium within the first 24 h. Once they have infiltrated the injured myocardium, neutrophils would then secret proteases that promote cardiac remodeling and chemokines that enhance the recruitment of monocytes from the spleen, in which the recruitment peaks at 72 h after myocardial infarction. Monocytes would transdifferentiate into macrophages after transmigrating into the infarct area. Both neutrophils and monocytes-derived macrophages are known to release proteases and cytokines that are detrimental to the surviving cardiomyocytes. Paradoxically, these inflammatory cells also play critical roles in repairing the injured myocardium. Depletion of either neutrophils or monocytes do not improve overall cardiac function after myocardial infarction. Instead, the left ventricular function is further impaired and cardiac fibrosis persists. Moreover, the inflammatory microenvironment created by the infiltrated neutrophils and monocytes-derived macrophages is essential for the recruitment of cardiac progenitor cells. Recent studies also suggest that treatment with anti-inflammatory drugs may cause cardiac dysfunction after injury. Indeed, clinical studies have shown that traditional ant-inflammatory strategies are ineffective to improve cardiac function after infarction. Thus, the focus should be on how to harness these inflammatory events to either improve the efficacy of the delivered drugs or to favor the recruitment of cardiac progenitor cells.